First-Time Application of Underwater Live Concrete for Economic Retrofitting of Damaged Bridge Piers in Bangladesh - S. Sowmik Islam; Quazi Umme Rukiya; Mirza Md Tasnim Mukarram (Advances in Civil Engineering)
This paper presents a comprehensive analysis of the use of underwater concrete (UWC) in the retrofitting restoration of bridge piers in Bangladesh. In Bangladesh, UWC is a comparatively new technology, and this investigation represents the first instance of its application in practice. This study’s primary objective was to produce self-compacting, self-fresh concrete with minimal mass loss. To accomplish this objective, antiwashout admixture (AWA) was added to the concrete mix at varying weight percentages (0.1%, 0.2%, 0.3%, 0.4%, and –0.5%) to determine the optimal dosage of AWA that would result in the least amount of concrete washout. The slump and runoff resistance of the concrete mixture were evaluated, and it was observed that a certain percentage of AWA addition resulted in minimal cement mass loss. Furthermore, cost reduction was a major concern of this study, as it is essential to minimize project expenses. Thus, comparative cost analyses of various repair techniques were conducted to determine the most cost-effective approach for future underwater repairs.